First detection of Theileria parva in cattle from Cameroon in the absence of the main tick vector Rhipicephalus appendiculatus - Silatsa, Barberine A.; Simo, G.; Githaka, Naftaly W.; Kamga, R.; Oumarou, F.; Tiambo, Christian K.; Machuka, Eunice M.; Domelevo Entfellner, Jean-Baka; Odongo, David O.; Bishop, Richard P.; Kuiate, Jules-Roger; Njiokou, F.; et al. (Hindawi Limited, 2020)
A major risk factor for the spread of livestock diseases and their vectors is the uncontrolled transboundary movement of live animals for trade and grazing. Such movements constrain effective control of tick-transmitted pathogens, including Theileria parva. Only limited studies have been undertaken to identify ticks and tick-borne diseases (TTBDs) affecting cattle in central African countries, including Cameroon. We hereby report the collection of baseline data on the prevalence of T. parva in Cameroon through a countrywide cross-sectional survey, conducted in 2016, involving collection of blood samples from cattle from 63 sites across the five agro-ecological zones (AEZs) of the country. ELISA-based surveillance of infected cattle was performed on 479 randomly selected samples and revealed specific antibodies to T. parva in 22.7% and T. mutans in 41.1% of cattle. Screening of 1,340 representative DNA samples for the presence of T. parva identified 25 (1.86%) positives using a p104 antigen gene-based nested PCR assay. The positives were distributed across agro-ecological zones I, II, III and V. None of the p104 positive cattle exhibited clinical symptoms of East Coast fever (ECF). Using reverse line blot (RLB), 58 (4.3%) and 1,139 (85%) of the samples reacted with the T. parva and T. mutans oligonucleotide probes, respectively. This represents the first report of T. parva from Cameroon. Surprisingly, no Rhipicephalus appendiculatus ticks, the main vector of T. parva, were identified in a parallel study involving comprehensive morphological and molecular survey of tick species present in the country. Only two of the 25 p104 positive cattle were PCR-positive for the CD8+ T-cell target schizont-expressed antigen gene Tp1. Cloning and sequencing of Tp1 amplicons revealed sequence identity with the reference T. parva Muguga. This new finding raises serious concerns of a potential spread of ECF into the central African region.